ANTHROPOCENTRIC PECULIARITIES OF DISCOURSE IN ADVERTISING - Qodirova Zaynab (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This essay contends that advertisement text is an essential component of society's socioeconomic and spiritual moral existence. Advertising text that meets human needs is now evaluated as the most common form of text. The commercial focuses on the text and stresses its meaning. To determine the linguistic and stylistic features of advertisement texts, a scientific analysis of its spheres of influence is needed. The article defines and explains the linguistic and stylistic characteristics of advertising texts, investigates approaches to the notion of "advertising text," and differentiates between advertising texts targeted at various audiences according to its age, occupation, and social purposes. It is shown that advertising texts can be categorized into many styles based on the size and method of coverage, the key elements of the ad text, the title plays an important role in the ad text, primarily attracting the buyer's interest. The text of the advertisement is brief, so the words in it are vivid, descriptive, and memorable. For product ads, the use of stylistic colored words and figurative phrases, in which nolinguistic means and language units are seen as means of forming advertising texts, is significant. The advertisement text stresses the importance of using word classes such as verbs and adjectives to illustrate the high quality of a product or service. Examples of punctuation in advertisement text are used to illustrate its function as a punctuation mark.